عنايةُ الصحَّابة بضبط الحديثِ دراسة تأصيلية - Said Yusuf Ahmed al-Subh; Mohammed Akhiruddin Ibrahim (Universiti Sains Islam Malaysia, 2024)
This study discusses the rigorousness of Sahaba in memorizing the Hadith of Prophet Muhammad peace be upon him. What is meant by memorization? What are its kinds? How did it happen? How did the Sahaba use to memorize the Hadith? What are the reasons for memorization? So this study aims at defining Hadith authentication, its kinds and the different reasons behind the rigorous memorization of the honorable Hadith by the Sahaba. This, in turn, will confirm for the future researchers the rigorousness in the link of Hadith Chain which is its starting point. The researcher has used the inductive method to clarify the reasons behind the strong points in authentication, which are included in the Hadith and their small parts of the general principles of the narrations. He also used the analytical method in studying the narrations. The researcher came up with two kinds of authentication: memorizing by the hearth and by writing, especially the Sahaba were known for their distinguished ability in memorization. This distinguished ability can be ascribed to different reasons; some of them are related to their own mental abilities, others ascribed to their closeness to the Prophet Muhammad peace be upon him and time and place (era). They (companions of the Prophet peace be upon him) memorized Al-hadith thoroughly, and they told these Hadith to the people carefully and rigorously. Over time, this has given the future researchers in Prophet Muhammad (peace be upon him) Hadiths' science the confidence and convenience in depending on the narrations in terms of the chain and its initiation where the revisionists and skeptics are paying attention.